Analysis of the halo background in femtosecond slicing experiments. (14th April 2016) - Schick, Daniel; Le Guyader, Loïc; Pontius, Niko; Radu, Ilie; Kachel, Torsten; Mitzner, Rolf; Zeschke, Thomas; Schüßler-Langeheine, Christian; Föhlisch, Alexander; Holldack, Karsten
Abstract : Besides femtosecond X‐ray pulses, synchrotron‐based laser‐slicing sources inherently produce a halo background with a different time structure, polarization and pointing direction. A detailed experimental characterization of this halo radiation at the FemtoSpeX facility at BESSY II is presented, and a method for its correct and unambiguous removal from femtosecond time‐resolved data using a dedicated laser triggering scheme as well as analytical models is demonstrated. Abstract : The slicing facility FemtoSpeX at BESSY II offers unique opportunities to study photo‐induced dynamics on femtosecond time scales by means of X‐ray magnetic circular dichroism, resonant and non‐resonant X‐ray diffraction, and X‐ray absorption spectroscopy experiments in the soft X‐ray regime. Besides femtosecond X‐ray pulses, slicing sources inherently also produce a so‐called `halo' background with a different time structure, polarization and pointing. Here a detailed experimental characterization of the halo radiation is presented, and a method is demonstrated for its correct and unambiguous removal from femtosecond time‐resolved data using a special laser triggering scheme as well as analytical models. Examples are given for time‐resolved measurements with corresponding halo correction, and errors of the relevant physical quantities caused by either neglecting or by applying a simplified model to describe this background are estimated.